Global Research Trends on School-Related Quality of Life among Adolescents: A Bibliometric Analysis - Lestari, Nur Eni; Herliana, Irma; Kartina, Irna (Universitas Pendidikan Indonesia, 2025)
Introduction: The quality of life of adolescents in schools is influenced by not only academic and physical health factors but also emotional, social, and psychological aspects shaped by relationships with peers, teachers, family, and the school environment. Objective: This study aims to map research trends on adolescents' quality of life in schools, identify key journals, and analyze researchers' contributions. Methods: A bibliometric analysis was conducted using data from Scopus, focusing on articles published over the past five years. The analysis includes co-occurrence, co-author, and citation analyses, visualized using VOSviewer and BiblioPlot software. Results: Research in this area has grown significantly, with increased activity in recent years, potentially informing better educational and health policies. Conclusions: Limited scientific collaboration among researchers hinders further progress. An interdisciplinary approach integrating psychology, education, public health, and sociology is crucial to understanding the complex factors impacting adolescents' quality of life, with a growing emphasis on psychosocial factors and mental health.